2020
DOI: 10.1017/dsd.2020.39
|View full text |Cite
|
Sign up to set email alerts
|

Users’ Survey for Development of Passenger Drones

Abstract: The prosperity of any megacities heavily depends on smooth transport systems. In India, however, most cities are failing to keep in step with the growing demands. With new technologies, such as passenger drones, an alternate mode of intra-city transportation seems within reach. For successful development of passenger drones in a diverse country like India, understanding users’ needs are vital. This paper presents the results from a survey of potential users of passenger drones from across India. These are then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Even though storyboarding is an established design research methodology and is well known in the design community, its use in the field of UAM research gives new insights to both design engineers and city planners. Four different working scenarios were created based on the combined knowledge gained from the literature review (Afonso et al 2021;Bauranov and Rakas 2021), user surveys (Rautray et al 2020), and studying white papers (Holden and Goel 2016). The user survey data were analysed by semantic decomposition and transformation followed by semantic mergence and supplement; finally, consistency scrutiny was done to improve the usability of the findings.…”
Section: Methodsmentioning
confidence: 99%
“…Even though storyboarding is an established design research methodology and is well known in the design community, its use in the field of UAM research gives new insights to both design engineers and city planners. Four different working scenarios were created based on the combined knowledge gained from the literature review (Afonso et al 2021;Bauranov and Rakas 2021), user surveys (Rautray et al 2020), and studying white papers (Holden and Goel 2016). The user survey data were analysed by semantic decomposition and transformation followed by semantic mergence and supplement; finally, consistency scrutiny was done to improve the usability of the findings.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain an overview of the potential factors that might affect passenger acceptance of HEAs, we merged our own findings with the results of other systematic reviews ( 2628 ) on passenger acceptance of conventional aviation, as well as in relation to new transport modes such as electric vehicles (EVs), autonomous vehicles (AVs), UAM/air taxis, and electric airplanes. We summarized the factors into five categories, including demographic factors, such as gender, age, education, employment, household income, household composition, and residential area ( 15, 21, 2732 ); travel behavior factors, such as travel frequency, in-vehicle time, mode choice, trip purpose, typical travel time spent, and mobility impairments ( 15, 17, 27, 28, 31, 33 ); situational/technological factors, such as speed, cost, power generation/supply, emissions (production and operation), safety, comfort, noise, turbulence/bumpiness, energy consumption, operation range, infrastructure, schedule reliability, and multimodal connectivity ( 15, 21, 2729, 31, 32, 34 ); attitudinal/psychological factors, such as personal innovativeness, environmental concern, perceived risks, social influence, trust, subjective norms (perceptions of others' behavior), moral norms, perceived usefulness, and perceived ease of use ( 15, 2629, 31, 33, 3537 ); and contextual factors, such as policy incentives, subsidies, and tax exemption ( 28 ). Two metareview papers ( 27 , 28 ) also concluded that the theory of planned behavior (TPB), the technology acceptance model (TAM), and the unified theory of acceptance and use of technology are the commonly applied theoretical models for studying the acceptance of AV and EV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these systems involve a certain degree of invasiveness and therefore the quality of human interaction with wearable systems becomes an important consideration from the product design point of view which necessitates the study of usability, product acceptance and overall user experience of these wearable systems. Over the past decade, there has been a growing emphasis on the aspect of human-centricity in the domain of research into design (Rautray et al, 2020). Therefore, there has been a focus on the study of various aspects such as usability, user experience design, human behaviour in design and the various methods of exploration for these aspects.…”
Section: Introductionmentioning
confidence: 99%